Conocimientos tributarios y evasión fiscal en comerciantes ambulantes del mercado Señor de los Milagros de la ciudad de Contamana, periodo 2024 - Arimuya Garcia, Antony Gabriel (2025)
The current study, "Tax Knowledge and Tax Evasion in Street Merchants of the Señor de los Milagros Market of the City of Contamana, Period 2024", aims to determine the relationship between the level of tax knowledge and Tax evasion among street merchants of that market. The study population of this research, quantitative and non-experimental in design, were street vendors who work in the Señor de los Milagros market. Relevant data was collected through a structured questionnaire to assess both tax knowledge and tax evasion practices. The objective of the investigation is to identify the main failures in the creation of taxes and the methods that merchants use to evade their tax obligations. In addition, it aims to provide practical suggestions to improve tax compliance and control and education measures that can be implemented by local authorities. This research is essential to understand the problem of tax evasion in the Señor de los Milagros market and to create effective policies that encourage the formalization and compliance of tax obligations among street vendors in Contamana.